Evaluation of sulfur mobility in soil Vitric haplustand - Bacca, Héctor Adrian; Narvaez, Juan Andrés; Unigarro S, Alberto (Revista de Ciencias Agrícolas, 2011)
In Pasto altiplano, there are grounds derived from volcanic ash in which agricultural activities have been intensified causing degradation and loss of nutrients that originate from the organic material of the ground. In laboratory conditions, the application of elemental sulfur, dehydrated calcium sulfate, magnesium sulfate, and ammonia sulfate was tested in quantities of 0,30,60 and 120 kg.ha-1 over the mobility of the SO4" ion and the change in the pH value. 128 samples of earth were taken from a depth of 30cm with PVC cylinders, which were incubated for 60 and 120 days. Elemental sulfur addition did not act on sulfur mobility and pH. After 60 days of incubation, sulfur availability depended upon the quantity added; 120 days later, SO24 ion distribution responded to the interaction source x quantity x evaluation depth. Ammonia sulfate being added, some differences were shown in sulfur availability in depth. With the utilization of calcium and magnesium sulfate, its availability was related to the sulfur quantity. After 60 and 120 days of incubation, pH depended on the interaction source x quantity x evaluation depth. 60 days after, pH changed in terms of depth when calcium sulfate was added and it responded to the amount of sulfur added and the evaluation depth with ammonia and magnesium sulfate. 120 days later, pH changed with the calcium and magnesium sulfate quantity and it depended on the amount and evaluation depth with ammonia sulfate.